Minimally Invasive Techniques in Myomectomy and Fertility Outcomes: A Narrative Review of the Current Evidence - Kyle G. Alexander; Sum-Yu C. Lee; Christien N. Haddad; Vasilios Tanos (IMR Press, 2024)
Objective: This narrative review aims to summarize the current evidence regarding fertility outcomes associated with different minimally invasive surgery (MIS) techniques in myomectomy. Mechanism: Uterine leiomyomas, commonly known as fibroids, are benign tumors affecting women of reproductive age. Surgery, particularly minimally invasive techniques, represents a definitive treatment for symptomatic fibroids, with preservation of fertility being a key consideration. MIS myomectomies, including laparoscopic, robotic-assisted laparoscopic myomectomy (RALM), and mini-laparotomy, are preferred over open laparotomy due to reduced morbidity and quicker recovery times. However, these procedures still carry risks, including uterine scar dehiscence and subsequent effects on pregnancy outcomes. Findings in Brief: Studies reviewed generally indicate favorable pregnancy outcomes across different MIS techniques, although with varying success rates. Conventional laparoscopy and RALM show promising pregnancy rates, akin to those observed with laparotomy. Nonetheless, higher numbers of fibroids removed during RALM correlate with increased rates of preterm births. The literature comparing laparotomy to laparoscopy, as well as across various MIS techniques, presents inconsistent results, likely due to the complexity and heterogeneity of fibroids, which can significantly impact fertility outcomes. Conclusions: Overall, myomectomy, irrespective of the approach employed, is generally associated with favorable fertility outcomes. While there are variations in success rates among different MIS techniques, no significant differences in the mode of delivery or the incidence of complications such as uterine rupture and adhesion formation are noted. Clinicians should consider individual patient factors when selecting the most appropriate technique for myomectomy. Ongoing advancements in surgical technology are likely to impact the landscape of MIS myomectomy and its implications for fertility outcomes. Further research and meta-analyses are warranted to clarify differences between MIS techniques and optimize patient outcomes.